The third way. (Economist, 2003)
This week Motorola, the world's second-largest handset maker, announced that it will soon launch a new handset, the MPx200, powered by Microsoft software. The news follows Motorola's decision last month to sell its stake in Symbian, an alliance it formed with Nokia and other top mobile-phone makers to provide a non-Microsoft operating system for high-end mobile phones, also known as smartphones. Like other handset firms, Motorola wants to avoid the fate of PC makers, which have become commodity box-shifters while Microsoft supplies the software and creams off the profit. Behind these tactical moves lies Motorola's real strategy: to go its own way, powering its handsets with a combination of Linux, an open-source operating system, and Java, a programming technology that allows software to run unchanged on multiple devices. Motorola expects to launch the first handsets based on this "MotoJUIX" combination (pronounced "Motojuice") next year.